Some Aspects of Mathematical Modeling of the Electromagnetic Field Influence on the Human Brain - Prigancová, Alina; Hvoždara, Michal; Túnyi, Igor; Gorgo, Yuriy; Mamilov, Sergii (Innovative Biosystems and Bioengineering, 2019)
Background. One of lacks of the use of high technologies is the megascopic level of unfavorable electromagnetic smog. Therefore, the study of influencing of the external electromagnetic field (EMF) is actual, within the limits of wide row of frequencies, on man's organs and brain. Objective. Modeling of influences on the brain of electric induction arising up at penetration of the EMF of a different frequency in the reserved sphere. Methods. A mathematical model of the EMF influence on human brain is considered. Namely, the model of a multi stratified sphere as an approximation of a human head is proposed. This sphere embedded into the unlimited nonconductive space (σ0 = 0) of the dielectric constant ε0. Skin and bones of head have a magnetic permeability of vacuum μ0. Influences on a brain are given as induction of the electric field, arising up at penetration of the variable electromagnetic field in the reserved sphere. Results. The results of numerical calculations for the three-layered model of head showed that induced of the electric field in the layer of brain has increased on the frequencies 107–108 Hz of external EMF. Distributions on the sphere of electromagnetic fields with f ≤ 106 Hz leave their amplitudes by unchanged regardless of depth of penetration. Fading of amplitudes shows up only for frequencies 107 and 108 Hz. Conclusions. Exposed in a model changes of electromagnetic waves on the frequencies 107–108 Hz can activate the parameters central nervous system and brain, that substantially will affect of man's activity. Will allow the further study of influencing of the electromagnetic field of a different frequency to identify to extent of brain activity, and also stress, positive and negative influencing of external EMF.